Climate Data Tools Training at AGRHYMET - Faniriantsoa, Rija (2016)
For more than three years, International Research Institute for Climate and Society (IRI) has collaborated with the AGRHYMET Regional Centre to improve of quality, accessibility and availability of climate data in West Africa. A training workshop on quality control methods for climate data and combination ground stations data with satellite rainfall estimates products using the earlier version of Climate Data Tools (CDT) was conducted for AGRHYMET staff in Niamey in July 2013. Since 2013, several improvements have been made on CDT and new features were added to facilitate the manipulation and visualization of data and generation of merged data. The present training came as the continuity of activities aimed at increasing the technical capacity of AGRHYMET staff to generate merged rainfall and temperature products with the new version of CDT. The main purpose of the training was to expose the participants to the new features of CDT, in order to strengthen capacity to conduct a quality control procedure for climate data at the level of their database, and combine ground stations data with global proxies (satellite rainfall estimates data and reanalysis product).